Additional Analgesia for Central Venous Catheter Insertion: A Placebo Controlled Randomized Trial of Dexmedetomidine and Fentanyl - Aloka Samantaray; Mangu Hanumantha Rao; Chitta Ranjan Sahu (Critical Care Research and Practice)
We aimed to show that a single preprocedural dose of either dexmedetomidine or fentanyl reduces procedural pain and discomfort and provides clinically acceptable sedation. In this prospective, double-blind study, sixty patients scheduled for elective surgery and requiring planned central venous catheter insertion were randomized to receive dexmedetomidine (1 μg/kg), fentanyl (1 μg/kg), or 0.9% normal saline intravenously over ten minutes followed by local anesthetic field infiltration before attempting central venous catheterization. The primary outcome measures are assessment and analysis of pain, discomfort, and sedation level before, during, and after the central venous catheter insertion at five time points. The median (IQR) pain score is worst for normal saline group at local anaesthetic injection [6 (4–6.7)] which was significantly attenuated by addition of fentanyl [3 (2–4)] and dexmedetomidine [4 (3–5)] in the immediate postprocedural period (P=0.001). However, the procedure related discomfort was significantly lower in dexmedetomidine group compared to fentanyl group in the first 10 min of procedure after local anaesthetic Injection (P=0.001). Fentanyl is more analgesically efficient for central venous catheter insertion along with local anaesthetic injection. However, dexmedetomidine has the potential to be superior to fentanyl and placebo in terms of providing comfort to the patients during the procedure.